Environment and methods of analysis external environment in the process of strategic management - Lukić, Jasmina (Hotel and Tourism Management, 2014)
Environment analysis is one of the key things for adequate strategic decision making. Managers start the process of defining a strategy by analyzing the external and internal environment. The external environment is a very specific segment of a company’s environment. A company does not have any influence on this type of environment, but only suffers the consequences caused by such a state. It either tries to adapt to it or perhaps to use such a situation to its advantage. This paper aims to highlight the importance of external environment when making strategic decisions and to point out the methods that can be used in this analysis. PEST and SWOT analysis are commonly used for the analysis of general environment, whereas the model of "five factors" is one of the tools used for analysis of competition environment.